Communities of energy. Issue 1 (January 2016) - Campbell, Ben; Cloke, Jon; Brown, Ed
Abstract : The call for social science to engage with energy infrastructures and users to enable low‐carbon transitions that benefit the poor in the Global South is welcome, but its urgency risks epistemic distortion. The theme of "community" in the social studies of energy needs critical reflection, disambiguation, and interrogation with empirical case studies. This article explores dimensions of assumed homogeneity at local scales. In attending to similarities and difference in comparisons between case studies in Nicaragua and Nepal, the authors propose that a framework for understanding communities of interest and practice can be identified in selective resistance to and appropriation of energy technologies that highlight positions of marginality and common purpose in emerging social energy systems.